Rumi and Aşkın Therapy - Ozdengul, Faik (Kültür A.S. Metropolitan Municipality of Konya, 2005)
This book shows Mawlana Jalaladdin Rumi as a life coach to modern people. Life skills Coaching is a professional field which has been increased fast among the modern psychology. People are looking for ways that can be easily adoptable to the life, more practical and a short cut in their rapid life. In that respect enlightened coaches are providing job for individuals, practical changes in personal and social life. In the present time athletes who are racing in Olympics have personal life coaches. Famous film stars, well-known artists, general managers, company owners, reach and successful people have also life coaches.